The Conceptual Resilience of the Atomistic Individual in Mainstream Economic Rationality (Review of Political Economy, 2025)
Τhe idea that social influences and social interactions play a central role on individual economic decisions has had a long presence in the history of economics. With the emergence of marginalism, this idea went into background and the concept of atomistic individual became established in mainstream economic rationality. Starting in the 1970’s, there were some attempts to reintroduce non-atomistic preferences in mainstream microeconomic theory in the form of social interactions, interdependent preferences, keeping up with the Joneses, social identity, social preferences, and status concerns. Social preferences have started to have a growing impact among mainstream microeconomics with the advent of behavioral economics, but still they are not in the hard core of the standard theory of choice. The paper argues that atomistic preferences are still prevalent, especially in the form of the assumption of representative agent. It also focuses on the role of methodological individualism and on the theoretical implications of relaxing the assumption of atomistic individual, as main explanations of the resilience of the mainstream economic rationality.